SELF-CONTROL SEBAGAI MODERASI ANTARA PENGETAHUAN KEUANGAN, FINANCIAL ATTITUDE, DAN UANG SAKU TERHADAP PERILAKU MENABUNG - Veronika Mardiana; Rochmawati Rochmawati (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2020)
The aim of this study is to investigate how financial knowledge, financial attitude, and pocket money can affect saving behavior with self-control as a moderate variable. This study adopted a quantitative approach. The population in this study was 298 students of Accounting Education Department at the State University of Surabaya with a sample of 178 students. The data collection methods were closed tests and questionnaires. The data were analyzed using Structural Equation Modeling (SEM) based on component partial least square (PLS) with the help of the WarpPLS 6.0 application. The results of the study show that: 1) financial knowledge does not significantly affect saving behavior and this is proven by p-value 0,348 ≥significant 0,05. 2) Financial attitude does not significantly affect saving behavior and this is proven by a p-value 0,225 ≥0,05. 3) pocket money has a significant impact on interest-bearing pocket money and this is demonstrated by p-value0,001 ≤0,01and Path Coefficient 0,754. 4) Self-control as moderating does not have a significant impact on saving behavior and this is proven by a p-value 0,148 ≥0,05. 5) Self-control is unable to modify the impact of financial knowledge on saving behavior and this is demonstrated by p-value 0 results, 0,207 ≥0,05. 6) Self-control can modernize financial attitude with saving behavior and this is proven by p-value 0,023 ≤ 0,05. 7) Self-control can modify the effect of pocket money on saving behavior and this is demonstrated by a p-value 0,047 ≤ 0,05.